2016
DOI: 10.1016/j.carbpol.2015.10.093
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polymer blends based on corn starch and thermoplastic chitosan processed by extrusion

Abstract: Blends of thermoplastic cornstarch (TPS) and chitosan (TPC) were obtained by melt extrusion. The effect of TPC incorporation in TPS matrix and polymer interaction on morphology and thermal and mechanical properties were investigated. Possible interactions between the starch molecules and thermoplastic chitosan were assessed by XRD and FTIR techniques. Scanning Electron Microscopy (SEM) analyses showed a homogeneous fracture surface without the presence of starch granules or chitosan aggregates. Although the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
136
3
16

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(171 citation statements)
references
References 43 publications
16
136
3
16
Order By: Relevance
“…The improvement of the mechanical properties of thermoplastic starch has been investigated by many researchers in recent years. Mendes et al (2016) developed the effect of incorporating thermoplastic chitosan (TPC) in a thermoplastic cornstarch (TPS) matrix on the mechanical properties of this material. The results show that it was possible to produce successfully corn starchchitosan blends by extrusion with high dispersion of the thermoplastic.…”
Section: Resultsmentioning
confidence: 99%
“…The improvement of the mechanical properties of thermoplastic starch has been investigated by many researchers in recent years. Mendes et al (2016) developed the effect of incorporating thermoplastic chitosan (TPC) in a thermoplastic cornstarch (TPS) matrix on the mechanical properties of this material. The results show that it was possible to produce successfully corn starchchitosan blends by extrusion with high dispersion of the thermoplastic.…”
Section: Resultsmentioning
confidence: 99%
“…Other work produced biodegradable polymer blends based on corn starch and thermoplastic chitosan extrusion processed, the resultant material presented a homogeneous fracture surface without the presence of starch granules or chitosan aggregates. Although the incorporation of thermoplastic chitosan caused a decrease in both tensile strength and stiffness, films with better extensibility and thermal stability were produced (Mendes et al, 2016). The previous research found that surface structure of chitosan/banana flour without crosslinking and prepare by casting method was exhibit big gel matrix particle because of retrogradation forms granula (Pitak & Rakshit,2011).…”
Section: Introductionmentioning
confidence: 99%
“…Starch-based bioplastic have been employed several sources, such as banana [1], potato [2], sago [2][3][4][5], rice [6], corn [7], soybean [8], and cassava [9]. Cassava starch has been broadly utilized to be used in bioplastic reinforced with clay nanoparticles [9], thermoplastic chitosan [7], poly lactic acid [10], gelatin [11], bamboo nanofibrils [12], bacterial cellulose [13], and green coconut fiber [14] in order to overcome drawbacks of starch-based bioplastic, such as mostly water-soluble, low resitancy, and low mechanical property. Cassava starch production generates by-product [9], i.e cassava bagasse or pulp consisted a fibrous material containing 30-60% residual starch [15].…”
Section: Introductionmentioning
confidence: 99%